The Effect Of Pressure On The Professional Performance Of Journalists Working In The Economic Field In Syrian Newspapers - Hallak, Boutros (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to identify the effect of pressure on the professional performance of journalists working in the economic field in Syrian newspapers. To achieve the objectives of the study were two questions are as follows - What are the main professional pressures facing journalists working in the economic field in Syrian newspapers? -What is the relationship of these variables (workload, organizational structure, wages and bonuses, labor relations) level of professional pressures facing journalists working for the economic domain in the Syrian press. And to answer the question the study was used "application form" the researcher prepared included several axes, according to the objectives of the study, which included research community all journalists working in the economic sphere, the Syrian central newspapers (public and private), whether they are full-time to this work or part-time, totaling from (197) journalist working in the economic field. After application of the tool and study the data and analyzed using appropriate statistical methods to collect reached the following conclusions: - The absence of adequate training commensurate with the expected performance of journalists Ka has the greatest impact on business performance. - The presence of more than one party intervenes in the press work and this contrasts with the principle of unity of command, and which constitutes one of the most important principles of administrative organization, and has led to a negative impact on the performance of journalists. - The wages and bonuses of the most important elements of professional pressures affecting the performance of the journalists, and it contradicts the nature of media work as an act of creative - Although there are a number of professional pressures, the Syrian journalists working in the economic field consider that their distinct and exceed the expectations of their superiors at work.